Persistence, Impairment, Disability and Unmet Treatment of Lifetime and 12-Month Anxiety Disorders in Black Men and Women, 50 Years of Age and Older. (June 2022) - Jones, Audrey L.; Rafferty, Jane; Cochran, Susan D.; Abelson, Jamie; Mays, Vickie M.
Objectives: To examine anxiety disorders in aging Black adults.Methods: Using nationally representative data from the National Survey of American Life, we estimated lifetime/12-month prevalence of anxiety disorders in Black men and women, age 50+ ( N = 1561). Disorder-specific persistence and severity, functional impairment, and mental health service utilization were investigated using multivariate regressions.Results: Black men and women who met criteria for anxiety disorders (lifetime prevalence=12.4%/18.3% in men/women) also demonstrated persistent disorders (percent meeting criteria = 40.3%–61.2%). Those with a 12-month anxiety disorder (6.2%/10.5% of men/women) typically reported severe task interference (38.3%–85.7%). Those with any 12-month anxiety disorder, compared to those without, experienced greater impairment in days out of role, work, family burden, cognition and, in women, mobility ( p 's < .05). Only 47.0%/65.2% of Black men/women with any lifetime anxiety disorder used mental health services.Discussion: Despite low prevalence, older Blacks with anxiety disorders experience substantial mental health burden in middle age and later.